Pengaruh Penggunaan Metode Jigsaw dan Minat Baca Terhadap Keterampilan Membaca Pemahaman pada Siswa Sekolah Dasar - Ummi Kalsum (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
This research is motivated by a phenomenon that occurs in the field, namely students have difficulty in reading comprehension. This can be seen from the low scores obtained by students in reading comprehension. This phenomenon makes researchers interested in conducting research. This study aims to obtain information about the effect of using the Jigsaw method and reading interest on reading comprehension skills for elementary school students. This type of research is quantitative research with a quasi-experimental method. Sampling technique The sample in the population is taken using the Simple Random Sampling (SRS) technique. The research data were collected using a reading interest questionnaire and a reading comprehension skill test. The results showed that: (1) the reading comprehension skills of students who were taught using the jigsaw method were higher than the students' reading comprehension skills taught by the conventional method, (2) the reading comprehension skills of students who had high reading interest taught by the jigsaw method were higher. than the reading comprehension skills of students who have high reading interest who are taught by conventional methods, (3) the reading comprehension skills of students who have low reading interest who are taught by the jigsaw method are higher than the reading comprehension skills of students who have low reading interest who are taught by conventional methods , and (4) there is no significant interaction between the jigsawl method and students' reading interest on reading comprehension skills. Based on the research conducted, it can be concluded that reading comprehension skills for elementary school students increase when using the jigsaw method and are associated with reading interest.